Răspunsuri

2014-09-06T16:45:23+03:00
A) 3(x-3)-8=20
3x-9-8=20
3x=20+8+9
3x=37 
⇒ x= 37/3 

b) 15-4(x+1)=10 
15-4x-4=10
15-4-10=4x
1=4x
⇒x=1/4

c)x-2= 1 intreg 1
      3                 15 
 
⇒x-2/3= 16/15 , aducem la acelasi numor (15) 
15x-10=16
15x= 16+10
15x= 26⇒x= 26/15. 

d) 3/4-x=1/12, aducem la numitor comun (12) 
 12-12x= 1
-12x= 1-12
-12x= -11
⇒x= 11/12

e)  7/18+x=19, aducem la numitor comun (18) 
7+18x=  342
x= (342-7):18
x= 335/18 

G) 
x*4/25=16/5
4x/25=16/5 
4x= 80
⇒ x= 80:4
x= 20.